HISTORICAL ORIGIN AND DEVELOPMENT OF POLITICALLY MOTIVATED CRIMINAL OFFENCES – POLITICAL DELICTS - Matić, Goran (Serbian political thought, 2024)
Keeping in mind the geopolitical developments in the first decade of the 21st century, migrant crisis, armed conflicts in Ukraine and the Gaza Strip, North African political changes and conflicts in the West, politically motivated protests in Serbia in the course of 2022, 2023 and 2024, politically motivated criminal offences - political delicts, as a neglected and forgotten category are gaining in importance. Public appearances, actions and conducts of certain social and political groups or individuals, disrespecting and violating the general social norms, dominant political system, constitutional order or an official ideology and religion, and calling for violent changes in the political system have always caused a particular reaction of the power elites through the criminal legislation and state system. The reaction of the power elites to these phenomena throughout history has been condemning and has most often led to general stigmatization and the harshest sanctions. Throughout history, before the inception, as well as after the formation of the state as a social creation, all regulated societies have considered these conducts socially dangerous and harmful, due to which they have been condemned and incriminated by regulations. The danger of political delicts directed through history against the ruling structures, social and religious systems has manifested itself in relation to the existing religious and social communities, and also to the basic values on which it was established, and, by the same token, to individual members of these communities, social classes and political elites that have established, prescribed, protected and shared these values. In accordance with the foregoing, it is quite clear that a social reaction has been developed and built up to reveal itself in different historical periods and to find expression in various manifestations of different degrees of intensity – from disapproval to formal general condemnation and sanctions. When observed through early historical epochs, the development of the criminal legal protection of the religious and social values of the society, and subsequently of the state, as a social creation, has nonetheless indisputably shown, despite all perceived anomalies of the power elites’ action, how politics manifested in terms of social and political repression, sometimes having both religious and ideological tint, has been finally subjected to law after all. One of the most important achievements of the European legal culture and thought from humanism and the Renaissance to the most recent times is the establishment of the concept and legal institute of political delict, as a privileged delict – criminal offence regulated by law, in terms of general and legal culture, despite the fact that it has been limited mainly to verbal political actions in democratic states. In contrast, other politically motivated criminal offences manifested as terrorism and extremism were removed from that structure at the end of the 20th century.
Keywords: politics; security; constitutional order; state; religion; law; human rights; criminal law; political delict; criminal offence; treason; high treason